2013
DOI: 10.1590/s1679-78252013000500008
|View full text |Cite
|
Sign up to set email alerts
|

Thermal flexural analysis of cross-ply laminated plates using trigonometric shear deformation theory

Abstract: Thermal stresses and displacements for orthotropic, two-layer antisymmetric, and three-layer symmetric square cross-ply laminated plates subjected to nonlinear thermal load through the thickness of laminated plates are presented by using trigonometric shear deformation theory. The in-plane displacement field uses sinusoidal function in terms of thickness co-ordinate to include the shear deformation effect. The theory satisfies the shear stress free boundary conditions on the top and bottom surfaces of the plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
4
6
0
Order By: Relevance
“…The transverse displacement is in good agreement with that of TSDT [44] for all aspect ratios. The in-plane normal stresses x ¯ y predicted by present theory are found to agree well with those of TSDT [44], whereas FSDT and CPT overestimate the same. The transverse shear stresses are obtained using equilibrium equations of elasticity to satisfy stress continuity at layer Table 2 Normalized displacements and stresses for two layered 0 /90 un-symmetric cross-ply laminated plate subjected to linear thermal load Through thickness distribution of in-plane displacement (ū), in-plane normal and shear stresses (¯ x ¯ y ¯ xy ) and transverse shear stresses (¯ xz ¯ yz ) for two layered 0 /90 un-symmetric crossply laminated composite plate with 2 / 1 = 3.…”
Section: Examplesupporting
confidence: 74%
See 4 more Smart Citations
“…The transverse displacement is in good agreement with that of TSDT [44] for all aspect ratios. The in-plane normal stresses x ¯ y predicted by present theory are found to agree well with those of TSDT [44], whereas FSDT and CPT overestimate the same. The transverse shear stresses are obtained using equilibrium equations of elasticity to satisfy stress continuity at layer Table 2 Normalized displacements and stresses for two layered 0 /90 un-symmetric cross-ply laminated plate subjected to linear thermal load Through thickness distribution of in-plane displacement (ū), in-plane normal and shear stresses (¯ x ¯ y ¯ xy ) and transverse shear stresses (¯ xz ¯ yz ) for two layered 0 /90 un-symmetric crossply laminated composite plate with 2 / 1 = 3.…”
Section: Examplesupporting
confidence: 74%
“…From the examination of Table 2 it is observed that the in-plane displacementsū andv predicted by present theory, TSDT of Ghugal and Kulkarni [44] and FSDT of Mindlin [13] are in close agreement with each other whereas CPT [12] underestimates the same for thick plate. The transverse displacement is in good agreement with that of TSDT [44] for all aspect ratios. The in-plane normal stresses x ¯ y predicted by present theory are found to agree well with those of TSDT [44], whereas FSDT and CPT overestimate the same.…”
Section: Examplesupporting
confidence: 56%
See 3 more Smart Citations